Character education management in learning in the boarding school - Astuti, Livia; Winarti, Agus (Technium Business and Management, 2023)
This study aims to describe the planning, implementation, and evaluation of character education in learning at the Al’Mumtaza Islamic boarding school, Kec. Cilengkrang Regency. Bandung. This type of research is descriptive qualitative to find out the process of character education in learning. Data sources are from boarding school administrators, teachers, parents, and students from various levels. Data collection techniques were observation, documentation, and in-depth interviews with informants. The validity of the research data was tested using data and informant triangulation. The analysis uses analytical techniques through data collection, condensation, presentation, and conclusion. The research results obtained: (1) character education planning in Islamic boarding school learning is carried out by Islamic boarding school managers by compiling the character values contained in the syllabus and lesson plans, including the central character values of God, others, the environment, sense of nationality, self, which translated into twenty main characters. (2) The implementation of character education in Islamic boarding schools is integrated with all subjects. The teacher inserts character values between learning activities. (3) Assessment of character education in learning in Islamic boarding schools is done daily by observing and giving assignments showing personality values that reflect the nation’s character.